(untitled) (World Bulletin of Management and Law, 2024)
In this article, the Author has provided information and opinions about the concept of "public order" in International Commercial Arbitration and commented on his knowledge. Also, the experience of countries where the concept of "public order" has been developed in international commercial arbitration has been considered.